Effectiveness of the Basic Education Remediation Kits on Improving the Reading Skills of Novice Readers - Stephanie Angela Aguirre; Chester Alexis C. Buama; Melvin T. Guache; Renniza F. Diola; Cristina E. Malabayabas; Jann Arlie P. Agawin (Journal of Elementary and Secondary School, 2024)
Remediation is crucial for strengthening students’ reading abilities, particularly for novice readers aged six to seven. Basic education practitioners must design intervention approaches that address reading and comprehension educational gaps. In response, this paper analyzed the effectiveness of the Basic Education Remediation Kits (BERKs) in improving the reading skills of struggling novice readers by revealing their reading skill level and revealing significant differences in the pre-test and post-test mean scores. The study employed a Quasi-experimental methodology with One-Group Pre-Test Post-Test Design and used purposive sampling as the sampling technique. The pre-/post-test consisted of two parts: 1) letter sounds and syllables and 2) short story with comprehension questions. The data was analyzed using descriptive statistics and paired samples t-tests to determine significant differences between the assessment results and the effectiveness of the remediation kit used. Findings revealed an increase in the students’ mean scores following kit implementation. The paired samples t-test confirmed a statistically significant difference between pretest and post-test scores, further affirming its effectiveness. The kit assists novice readers, particularly those in the early stages of literacy; nevertheless, its effectiveness varies according to reading level; thus, the use of a single teaching strategy may not be equally beneficial to all students. The long-term impact of the remediation kit may be evaluated considering aspects such as intervention duration, teaching pedagogy, and demographics. A group of participants with the same reading level may be used to further assess its efficacy.